Optoelectronic device and method of manufacturing the same
Patent Information
- Application Number
- CN202511985591.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-24
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]然而现有光电器件中还存在启亮电压较高等问题,有待进一步改善
[0010]本申请提供的光电器件的启亮电压较低,且具有较长的使用寿命等。
Smart Images

Figure CN122909970A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of display technology, and in particular to an optoelectronic device and its fabrication method. Background Technology
[0002] Currently, the most widely used light-emitting devices are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). OLEDs have become the mainstream technology in the field of display technology due to their excellent display performance, including self-illumination, simple structure, ultra-thinness, fast response speed, wide viewing angle, low power consumption, and flexible display capabilities. QLEDs have the advantages of saturated emitted light color and tunable wavelength, and also have high quantum yields in photoluminescence and electroluminescence, making them a strong competitor to OLEDs in recent years.
[0003] Traditional OLED and QLED device structures generally include an anode, a hole injection layer, a hole transport layer, an emissive layer, an electron transport layer, an electron injection layer, and a cathode. Under the influence of an electric field, holes generated at the anode and electrons generated at the cathode of the LED move and are injected into the hole transport layer and electron transport layer, respectively, and eventually migrate to the emissive layer. When the two meet in the emissive layer, they generate excitons, which excite the light-emitting molecules to ultimately produce visible light.
[0004] However, existing optoelectronic devices still have problems such as high start-up voltage, which need to be further improved. Summary of the Invention
[0005] In view of this, this application provides an optoelectronic device and a method for fabricating the same.
[0006] The embodiments of this application are implemented as follows: an optoelectronic device includes an anode, a light-emitting layer, an electronic functional layer, an interface layer, and a cathode arranged sequentially.
[0007] Accordingly, embodiments of this application also provide a method for fabricating an optoelectronic device, comprising the following steps: An anode, a light-emitting layer, and an electronic functional layer are sequentially arranged; an interface layer is formed on the electronic functional layer; and a cathode is formed on the interface layer to obtain a photoelectric device.
[0008] Accordingly, this application also provides another method for fabricating an optoelectronic device, comprising the following steps: A cathode is provided; an interface layer is formed on the cathode; an electronic functional layer, a light-emitting layer, and an anode are sequentially formed on the interface layer to obtain an optoelectronic device.
[0009] The electronic functional layer is made of N-type inorganic nanoparticles. The interface layer is made of a first metal salt and a second metal salt, wherein the metal ions in the first metal salt include fourth-period metal ions, and the metal ions in the second metal salt include one or more of alkali metal ions and alkaline earth metal ions. The cathode includes a first metal electrode.
[0010] The optoelectronic device provided in this application has a low start-up voltage and a long service life. Attached Figure Description
[0011] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0012] Figure 1 This is a schematic diagram of the structure of an optoelectronic device provided in an embodiment of this application; Figure 2 This is a flowchart illustrating a method for fabricating an optoelectronic device according to an embodiment of this application; Figure 3 This is a flowchart of a method for fabricating an optoelectronic device provided in an embodiment of this application.
[0013] Figure label: 100 - Optoelectronic device; 10 - Anode; 20 - Hole functional layer; 21 - Hole injection layer; 22 - Hole transport layer; 30 - Light emission layer; 40 - Electronic functional layer; 50 - Interface layer; 60 - Cathode. Detailed Implementation
[0014] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. Furthermore, it should be understood that the specific embodiments described herein are only for illustration and explanation of this application and are not intended to limit this application.
[0015] In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in its actual use or operating state, specifically the orientation shown in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative purposes and do not impose numerical requirements or establish a numerical order.
[0016] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.
[0017] In this application, "at least one" means one or more, and "more than one" means two or more. "One or more", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0018] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.
[0019] The thickness of the film layer in this application was tested according to the national standard GB / T36969-2018. The particle size of the N-type inorganic nanoparticles in this application was tested according to the national standard GBT / 29022-2021.
[0020] Currently, during the aging process of optoelectronic devices under power-on conditions, the conductivity defects of materials in the electronic functional layer, such as ZnO, continuously increase with the application of power, leading to a continuous increase in transmission capacity. However, the hole transmission capacity of the hole functional layer is relatively weak, causing the carrier balance to be continuously disrupted under power-on conditions. This exacerbates the carrier imbalance, resulting in a shorter lifespan for optoelectronic devices and hindering their commercialization. Furthermore, when optoelectronic devices are turned on, the carrier injection barrier is usually too high, which increases the turn-on voltage, leading to low luminous efficiency and a roll-off in external quantum efficiency. The continuous high electric field can also cause physical damage to the functional layers and interfaces of the optoelectronic device, inducing more defects and creating a vicious cycle of performance degradation, severely affecting the lifespan of the optoelectronic device.
[0021] The technical solution of this application is as follows: Firstly, please refer to Figure 1 This application provides an optoelectronic device 100, which includes an anode 10, a light-emitting layer 30, an electronic functional layer 40, an interface layer 50 and a cathode 60 arranged sequentially.
[0022] The electronic functional layer 40 is made of N-type inorganic nanoparticles.
[0023] The material of the interface layer 50 includes a first metal salt and a second metal salt. The metal ions in the first metal salt include fourth-period metal ions, and the metal ions in the second metal salt include one or more of alkali metal ions and alkaline earth metal ions.
[0024] The cathode 60 includes a first metal electrode.
[0025] In the optoelectronic device 100 provided in this application, an interface layer 50 is introduced between the electronic functional layer 40 and the cathode 60. The metal ions of the second metal salt in the interface layer 50 include one or more of alkali metal ions and alkaline earth metal ions. Alkali metal ions and alkaline earth metal ions have lower surface potentials. At the instant the optoelectronic device 100 is turned on, the interface layer 50 can act as a step film layer between the cathode 60 and the electronic functional layer 40, making it easier for electrons to be injected from the cathode 60 into the electronic functional layer 40, thereby reducing the turn-on voltage of the optoelectronic device 100 and improving the luminous efficiency of the optoelectronic device 100. During the operation of the optoelectronic device 100, the electron transport capability of the N-type inorganic nanoparticles in the electronic functional layer 40 will continuously increase. By introducing the interface layer 50, this solution can effectively counteract the increase in the electron transport capability of the N-type inorganic nanoparticles caused by energization, thereby maintaining the dynamic balance of charge carriers and effectively extending the service life of the optoelectronic device 100. The applicant speculates that the possible reason is that the metal ions of the first metal salt in the interface layer 50 include fourth-period metal ions. The fourth-period metal ions can react with the first metal electrode of the cathode 60, causing the first metal electrode to generate a metal compound. The electron injection rate of the metal compound generated by the first metal electrode is low, which causes the electron injection capability to decrease slowly, thereby effectively regulating the electron transport capability of the electron functional layer 40.
[0026] In the interface layer 50 provided in this application, the second metal salt acts on the optoelectronic device 100 when it is turned on, while the first metal salt acts on the optoelectronic device 100 during its power-on operation, effectively reducing the turn-on voltage of the optoelectronic device 100, improving the luminous efficiency of the optoelectronic device 100, and extending the service life of the optoelectronic device 100.
[0027] It should be noted that the reaction between the first metal salt and the first metal electrode may involve multiple mechanisms. The following examples illustrate this with zinc acetate as the first metal salt, silver as the first metal electrode, and ZnO as the N-type inorganic nanoparticle.
[0028] During the energizing process, a displacement reaction may occur between zinc acetate in the interface layer 50 and the silver electrode, with the reaction formula: (CH3COO)2Zn + 2Ag === 2CH3COOAg + Zn. Silver acetate can effectively reduce electron injection. This electrochemical reaction after energizing is extremely slow, occurs under energizing conditions, and is generally irreversible, which is consistent with the operating characteristics of the optoelectronic device 100. It will not cause changes in the internal potential barrier due to storage, thus preventing instability of the optoelectronic device 100 during storage. The displacement reaction during energizing counteracts the increase in electron transport capacity of the N-type inorganic nanoparticles under energizing conditions, effectively maintaining a dynamic charge balance.
[0029] Zinc acetate readily absorbs water to form hydrated zinc acetate. During the fabrication of optoelectronic device 100, water molecules may be introduced into the interface layer 50 due to environmental factors or other water-containing materials or solvents. These water molecules react with zinc acetate to form hydrated zinc acetate. During the heat treatment of optoelectronic device 100, the water in the hydrated zinc acetate may be released, serving as an intermediate reaction medium between zinc oxide and silver. This forms a reverse reaction similar to that of a zinc-silver button cell, with the reaction formula speculated to be: 2Ag + ZnO === Ag2O + Zn. In other words, silver oxide and zinc are formed under energized conditions. Silver oxide can play a similar role to silver acetate, effectively reducing electron injection and thus significantly improving the lifespan of optoelectronic device 100.
[0030] In some embodiments, the optoelectronic device 100 may be an upright optoelectronic device 100 or an inverted optoelectronic device 100.
[0031] In some embodiments, the optoelectronic device 100 may be a light-emitting diode.
[0032] In some embodiments, the average particle size of the N-type inorganic nanoparticles is 3nm to 15nm, for example, it can be 3nm, 5nm, 8nm, 10nm, 12nm, 15nm or any range between two of the above values.
[0033] In some embodiments, the N-type inorganic nanoparticles include one or more of the following: first doped metal oxide particles, first undoped metal oxide particles, non-metal nitrides, group IIB-VIA semiconductor materials, group IIIA-VA semiconductor materials, and group IB-IIIA-VIA semiconductor materials. The first undoped metal oxide particles are made of one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and HfO2. The metal oxide in the first doped metal oxide particles is made of one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, HfO2, and Al2O3. The doping element in the first doped metal oxide particle includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, Cd, and Cs. The molar fraction of the doping element in the first doped metal oxide particle is 1% to 20%. The non-metallic nitride includes Si3N4. The IIB-VIA group semiconductor material includes one or more of ZnS, ZnSe, and CdS. The IIIA-VA group semiconductor material includes one or more of InP and GaP. The IB-IIIA-VIA group semiconductor material includes one or more of CuInS and CuGaS.
[0034] It should be noted that the molar fraction of the doping element in the first doped metal oxide particle refers to the number of moles of the doping element divided by (the sum of the number of moles of the doping element and the number of moles of the metal in the metal oxide of the first doped metal oxide particle). For example, the molar fraction of Mg-doped ZnO is 5%, which can be expressed as Zn 0.95 Mg 0.5 O.
[0035] In some embodiments, the fourth-period metal ions include one or more of zinc ions, chromium ions, and manganese ions.
[0036] In some embodiments, the anions in the first metal salt include one or more of acetate ions, formate ions, propionate ions, halide ions, nitrate ions, and sulfate ions.
[0037] Further, the first metal salt comprises one or more of a first organic acid salt and a first inorganic acid salt. The organic acid salt comprises one or more of zinc acetate, zinc formate, zinc propionate, chromium acetate, chromium formate, chromium propionate, manganese acetate, manganese formate, and manganese propionate. The inorganic acid salt comprises one or more of zinc chloride, zinc nitrate, zinc sulfate, chromium chloride, chromium nitrate, chromium sulfate, manganese chloride, manganese nitrate, and manganese sulfate.
[0038] In some embodiments, the alkali metal ions include one or more of lithium ions, sodium ions, and potassium ions.
[0039] In some embodiments, the alkaline earth metal ions include one or more of magnesium ions and calcium ions.
[0040] In some embodiments, the anions in the second metal salt include one or more of acetate ions, formate ions, propionate ions, oxalate ions, malonate ions, halide ions, nitrate ions, and sulfate ions.
[0041] Further, the second metal salt comprises one or more of a second organic acid salt and a second inorganic acid salt. The organic acid salt comprises one or more of lithium acetate, lithium formate, lithium propionate, lithium oxalate, lithium malonate, sodium acetate, sodium formate, sodium propionate, sodium oxalate, sodium malonate, potassium acetate, potassium formate, potassium propionate, potassium oxalate, potassium malonate, magnesium acetate, magnesium formate, magnesium propionate, magnesium oxalate, magnesium malonate, calcium acetate, calcium formate, calcium propionate, calcium oxalate, and calcium malonate. The inorganic acid salt comprises one or more of lithium chloride, lithium bromide, lithium fluoride, lithium nitrate, lithium sulfate, sodium chloride, sodium bromide, sodium sulfate, sodium nitrate, potassium chloride, potassium bromide, potassium sulfate, potassium nitrate, magnesium chloride, magnesium nitrate, magnesium sulfate, calcium chloride, calcium nitrate, and calcium sulfate.
[0042] In some embodiments, the material of the first metal electrode includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, Mg, and Pt.
[0043] The first metal salt and the first metal electrode provided in this application can react with each other under energization, effectively reducing electron injection.
[0044] In some embodiments, the material in the optoelectronic device 100 further includes a third metal salt, which is obtained by reacting the first metal salt with the first metal electrode. The third metal salt is located in the cathode 60. Correspondingly, the reaction between the first metal salt and the first metal electrode may also displace the first metal (such as Zn in (CH3COO)2Zn). 2+ →Zn), the first metal is located in the interface layer 50.
[0045] For example, the third metal salt includes one or more of aluminum salt, silver salt, copper salt, molybdenum salt, gold salt, barium salt, calcium salt, ytterbium salt, magnesium salt, and platinum salt, and the first metal includes one or more of zinc, chromium, and manganese.
[0046] In some embodiments, the material in the optoelectronic device 100 further includes a metal oxide, which is obtained by reacting the N-type inorganic nanoparticles with the first metal electrode. The metal oxide is located between the interface layer 50 and the cathode 60. Correspondingly, the reaction between the N-type inorganic nanoparticles and the first metal electrode also generates a second metal (such as Zn in ZnO). 2+ →Zn), the second metal is located in the electronic functional layer 40. It is understood that the content of metal oxide is small, existing between the interface layer 50 and the cathode 60, and will not form a distinct, continuous, and clearly defined film.
[0047] For example, the metal oxide includes one or more of aluminum oxide, silver oxide, copper oxide, molybdenum oxide, gold oxide, barium oxide, calcium oxide, ytterbium oxide, magnesium oxide, and platinum oxide, and the second metal includes one or more of zinc, titanium, tin, zirconium, tantalum, and hafnium.
[0048] In some embodiments, the mass ratio of the first metal salt to the second metal salt in the interface layer 50 is (1~4):(1~4), for example, it can be 1:4, 2:3, 1:1, 3:2, 4:1, or any range between two of the above ratios. Within the range of the mass ratio, the first metal salt and the second metal salt cooperate with each other to effectively reduce the turn-on voltage of the optoelectronic device 100, improve the luminous efficiency of the optoelectronic device 100, and extend the service life of the optoelectronic device 100.
[0049] In some embodiments, the electronic functional layer 40 includes an electronic transport layer.
[0050] In some embodiments, the average thickness of the electronic functional layer 40 is 10nm to 100nm, for example, it can be 10nm, 20nm, 50nm, 60nm, 80nm, 100nm or any range between two of the above values.
[0051] In some embodiments, the average thickness of the interface layer 50 is 0.5 nm to 10 nm, for example, it can be 0.5 nm, 1 nm, 2 nm, 5 nm, 8 nm, 10 nm, or any range between two of the above values. Within the range of the thickness of the interface layer 50, the interface layer 50 is relatively thin, which can avoid increasing the voltage of the optoelectronic device 100 itself due to poor conductivity.
[0052] In some embodiments, the average thickness of the cathode 60 is 20nm to 200nm, for example, it can be 20nm, 50nm, 80nm, 100nm, 150nm, 200nm or any range between two of the above values.
[0053] In some embodiments, the material of the electronic functional layer 40 further includes a crosslinking agent.
[0054] In some embodiments, the crosslinking agent comprises a polythiol crosslinking agent.
[0055] Further, the multi-thiol crosslinking agent includes one or more of pentaerythritol tetrakis(3-mercaptopropionic acid) ester (PETMP), tris[2-(3-mercaptopropoxy)ethyl isocyanurate], trimethylolpropane tris(3-mercaptopropionate) ester (TMPMP), and dipentaerythritol hexa(3-mercaptopropionic acid) ester.
[0056] In some embodiments, the crosslinking agent and the N-type inorganic nanoparticles are coordinated and linked. Specifically, multiple thiol groups in the crosslinking agent can be coordinated and linked to metal ions in different N-type inorganic nanoparticles, thereby crosslinking and linking multiple N-type inorganic nanoparticles, improving the density and stability of the electronic functional layer 40, and making it less susceptible to solvent erosion and dissolution after film formation.
[0057] In some embodiments, the mass ratio of the N-type inorganic nanoparticles to the crosslinking agent in the electronic functional layer 40 is (90~99):(1~10), for example, it can be 90:10, 92:8, 95:5, 98:2, 99:1, or any range between two of the above ratios. Within the range of the mass ratio, the crosslinking agent can effectively promote the crosslinking of the N-type inorganic nanoparticles and improve the stability of the electronic functional layer 40.
[0058] In some embodiments, the anode 10 is an anode 10 known in the art for use in optoelectronic devices 100, and may include one or more of a second metal electrode, a carbon material electrode, a metal oxide electrode, and a composite electrode. The material of the second metal electrode includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, and Mg; the material of the carbon material electrode includes one or more of graphite, carbon nanotubes, graphene, and carbon fibers; and the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3, and AMO. The composite electrode is a composite electrode in which a metal layer is sandwiched between layers of doped or undoped transparent metal oxide particles. The composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2, etc., where " / " indicates a stacked structure. For example, AZO / Ag / AZO represents a composite electrode that includes a sequentially stacked AZO layer, an Ag layer, and an AZO layer.
[0059] In some embodiments, the material of the light-emitting layer 30 includes organic light-emitting materials or quantum dots.
[0060] The organic light-emitting material may be selected from, but is not limited to, one or more of the following: CBP:Ir(mppy)3 (4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridinium(III)]), TCTX:Ir(mmpy) (4,4',4''-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridinium(III)]), diaromatic anthracene derivatives, stilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF (thermally activated delayed) materials, polymers containing BN covalent bonds, HLCT (hybrid local charge transfer excited state) materials, and Exciplex (exciplex) light-emitting materials.
[0061] The quantum dots may be selected from, but are not limited to, one or more of single-structure quantum dots, core-shell structure quantum dots, and perovskite quantum dots.
[0062] The materials for the single-structure quantum dots, the core material of the core-shell quantum dots, and the shell material of the core-shell quantum dots can be selected from, but are not limited to, one or more compounds from group II-VI, group IV-VI, group III-V, and group I-III-VI. The shell of the core-shell quantum dots may consist of one or more layers. The group II-VI compounds may be selected from, but are not limited to, one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe. The IV-VI group compounds may be selected from, but are not limited to, one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The group III-V compounds may be selected from, but are not limited to, one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. The group I-III-VI compounds may be selected from, but are not limited to, one or more of CuInS2, CuInSe2, and AgInS2.
[0063] As an example, the core-shell structured quantum dots can be selected from, but are not limited to, one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS, and InP / ZnSe / ZnS. In the above descriptions of CdSe / ZnS, etc., the " / " indicates that the material after the " / " (as the shell) covers the material before the " / " (as the core).
[0064] The materials used for the perovskite quantum dots can be selected from, but are not limited to, doped or undoped inorganic perovskite semiconductors or organic-inorganic hybrid perovskite semiconductors. The general structural formula of the inorganic perovskite semiconductor is AMX3, where A is Cs. + Ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ Cu 2+ Ni 2+ Cd 2+ Cr 2+ Mn 2+ Co 2+ Fe 2+ 、Ge 2 + Yb 2+ Eu 2+ One or more of the following, where X is a halide anion selected from Cl... - ,Br - I - One or more of the following. The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, where B is an organic amine cation selected from CH3(CH2). n-2 NH3 + Or [NH3(CH2)] n NH3] 2+ Where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ Cu 2+ Ni 2+ Cd 2+ Cr 2+ Mn 2+ Co 2+ Fe 2+ 、Ge 2+ Yb 2+ Eu 2+ One or more of the following, where X is a halide anion selected from Cl... - ,Br - I- One or more of them.
[0065] In some embodiments, the optoelectronic device 100 further includes a hole functional layer 20, which is located between the anode 10 and the light-emitting layer 30.
[0066] In some embodiments, the hole functional layer 20 includes one or more of a hole injection layer 21 and a hole transport layer 22, wherein the hole injection layer 21 is located between the anode 10 and the hole transport layer 22.
[0067] Furthermore, the material of the hole injection layer 21 is a material known in the art for use in hole injection layers 21, such as one or more selected from high-conductivity organic molecular materials, transition metal oxides, and transition metal sulfur compounds; the high-conductivity organic molecular material is selected from poly(3,4-ethylenedioxythiophene) (PEDOT), poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazabenzphenanthrene, copper polyester carbonate, free phthalocyanine (H2PC), copper phthalocyanine (CuPc), platinum phthalocyanine (PtPC), and titanium phthalocyanine (TiOP). C) 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazabenzophenanthrene (HAT-CN), 7,7,8,8-tetracyano-p-benzodiquinone dimethyl ether (TCNQ), N,N'-bis[4-(diphenylamino)phenyl]-N,N'-di-1-naphthyl-biphenyl-4,4'-diamine (NPB-DPA), N,N'-diphenyl-N,N'-di(4'-(N,N-di(1- Naphthyl)-amino)-4-biphenyl)-benzidine (Di-NPB), N,N′-di(phenyl)-N,N′-di(4′-(N,N-di(phenylamino)-4-biphenyl)benzidine (TPT1), N,N'-diphenyl-N,N'-di-[4-(N,N-di-p-tolylamino)phenyl]benzidine (NTNPB), N4,N4,N4',N4'-tetra(4-methoxyphenyl)-[1,1'- The transition metal oxide is selected from one or more of the following: [biphenyl]-4,4'-diamine (MeO-TPD), 4,4',4''-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), 4,4'4"-tris(N,N-diphenylamino)triphenylamine (NATA), N2,N2'-(9,9-dimethyl-9H-fluorene-2,7-diyl)bis(9,9-dimethyl-N2,N7,N7-triphenyl-9H-fluorene-2,7-diamine) (3DMFL-BPA), and 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone (F4-TCNQ); the transition metal oxide is selected from one or more of NiO, MoO3, WO3, CuO, and Cu2O; the transition metal chalcogenide compound is selected from one or more of MoS2, MoSe2, WS3, WSe3, and CuS.
[0068] The material of the hole transport layer 22 is a material known in the art for use in hole transport layers 22, and may include one or more of organic hole transport materials and inorganic hole transport materials. The organic hole transport materials include poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), poly(9-vinylcarbazole) (PVK), 9,9'-(1,3-phenyl)bis-9H-carbazole (mCP), 4,4',4''-tris(carbazole-9-yl)triphenylamine (TCTA), and 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline]. (TAPC), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), N,N'-di(naphthyl-2-yl)-N,N'-di(phenyl)biphenyl-4,4'-diamine (B-NPB), N2,N7-di-1-naphthyl-N2,N7-diphenyl-9,9'-spirodi[9H-fluorene]-2,7-diamine (Spiro-NPB), N2,N7-DI-1-naphthyl-N2,N7,9,9-tetraphenyl-9H-fluorene-2,7-diamine (DPFL- NPB), 9,9-di(2-ethylhexyl)-N,N'-di-1-naphthyl-N,N'-diphenyl-9H-fluorene-2,7-diamine (DOFL-NPB), N4,N4'-di(4-vinylphenyl)-N4,N4'-di-1-naphthylbiphenyl-4,4'-diamine (VNPB), 3,6-bis(9-phenyl-9H-carbazol-3-yl)-9-phenyl-9H-carbazole (Tris-PCz), 9,1-dihydro-9,9-dimethyl-1-(9-phenyl-9H-carbazol-3-yl)-pyridine (PC) zAc), N-biphenyl-4-yl-9,9-dimethyl-N-[4-(9-phenyl-9H-carbazol-3-yl)phenyl]-9H-fluorene-2-amine (PCbz-PA1), 9,9-dimethyl-N,N'-bis(3-methylphenyl)-N,N'-diphenyl-9H-fluorene-2,7-diamine (DMFL-TPD), N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), N,N'-bis(3-methylphenyl)-N,N'-diphenyl-9, 9-Spiro-difluorene-2,7-diamine (Spiro-TPD), N,N,N',N'-tetra(2-naphthyl)-1,1'-biphenyl-4,4'-diamine (β-TNB), 2,2',7,7'-tetra(diphenylamino)-9,9'-spirobisfluorene (Spiro-TAD), N,N'-bis(9,9-dimethyl-9H-fluorene-2-yl)-N,N'-diphenylbenzidine (BF-DPB), N,N,N',N'-tetraphenylbenzidinediamine (BPBPA), 4,4'-(diphenylmethylene)bis(N,N-Diphenylaniline (TCBPA), 9,9-bis[4-[bis(bis(biphenyl-4-yl)amino]phenyl]fluorene (BPAPF), tris(4-biphenyl)amine (TBA), 4,4'-(diphenylsilanediyl)bis(N,N-diphenylaniline) (TSBPA), 4,4'-(9H-fluorene-9-alkylene)bis[N,N-bis(4-methylphenyl)-aniline (DTAF), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine, poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4'-bis(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine; the inorganic hole transport material includes doped graphene, undoped graphene, C, 60 The metal oxide particles are selected from one or more of the following: a second doped metal oxide particle, a second undoped metal oxide particle, a metal sulfide, a metal selenide, and a metal nitride. The metal oxides in the second doped metal oxide particle and the second undoped metal oxide particle each independently include one or more of MoO3, WO3, NiO, CrO3, CuO, Cu2O, and V2O5. The doping element in the second doped metal oxide particle includes one or more of Mo, W, Ni, Cr, Cu, and V. The metal sulfide includes one or more of CuS, MoS3, and WS3. The metal selenide includes one or more of MoSe3 and WSe3. The metal nitride includes p-type gallium nitride.
[0069] Secondly, this application also provides a method for preparing an optoelectronic device 100, which can prepare the above-mentioned optoelectronic device 100.
[0070] In some embodiments, please refer to Figure 2 The method for fabricating the optoelectronic device 100 includes the following steps: Step S11: Provide an anode 10, a light-emitting layer 30, and an electronic functional layer 40 arranged sequentially; Step S12: Form an interface layer 50 on the electronic functional layer 40; Step S13: Form a cathode 60 on the interface layer 50 to obtain a photoelectric device 100.
[0071] It can be understood that the optoelectronic device 100 prepared by the above preparation method is an upright optoelectronic device 100.
[0072] In other embodiments, please refer to Figure 3The method for fabricating the optoelectronic device 100 includes the following steps: Step S21: Provide a cathode 60; Step S22: Form an interface layer 50 on the cathode 60; Step S23: An electronic functional layer 40, a light-emitting layer 30, and an anode 10 are sequentially formed on the interface layer 50 to obtain an optoelectronic device 100.
[0073] It can be understood that the optoelectronic device 100 prepared by the above preparation method is an inverted optoelectronic device 100.
[0074] In both of the above preparation methods, the material of the electronic functional layer 40 includes N-type inorganic nanoparticles.
[0075] The material of the interface layer 50 includes a first metal salt and a second metal salt. The metal ions in the first metal salt include fourth-period metal ions, and the metal ions in the second metal salt include one or more of alkali metal ions and alkaline earth metal ions.
[0076] The cathode 60 is made of a first metal electrode.
[0077] The materials for each functional layer and interface layer 50 are described above and will not be repeated here.
[0078] It should be noted that the anode 10, light-emitting layer 30, electronic functional layer 40, interface layer 50, and cathode 60 can be implemented using conventional techniques in the art, such as chemical or physical methods. Chemical methods include chemical vapor deposition, continuous ion layer adsorption and reaction, anodic oxidation, electrolytic deposition, and co-precipitation. Physical methods include physical coating and solution methods. Physical coating methods include thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion plating, physical vapor deposition, atomic layer deposition, and pulsed laser deposition, etc. Solution methods can include spin coating, printing, inkjet printing, blade coating, dip coating, immersion coating, spraying, roller coating, casting, slot coating, and strip coating, etc.
[0079] Exemplary, in some embodiments, the method for fabricating the electronic functional layer 40 in the sequentially arranged anode 10, light-emitting layer 30, and electronic functional layer 40 includes: A first mixture is provided, the first mixture comprising the N-type inorganic nanoparticles, a crosslinking agent, and a first solvent; The first mixture is deposited to obtain the electronic functional layer 40.
[0080] The crosslinking agent can be found above and will not be repeated here.
[0081] In some embodiments, the first solvent comprises a polar solvent. Further, the polar solvent is selected from C1-C2. 10 Alcohol solvents. Furthermore, the C1-C... 10 The alcohol solvent is selected from one or more of methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, trimethoxybutanol, triethylene glycol monobutyl ether, and diethylene glycol dimethyl ether.
[0082] In some embodiments, the mass concentration of the N-type inorganic nanoparticles in the first mixture is 10 mg / mL to 80 mg / mL, for example, it can be 10 mg / mL, 20 mg / mL, 40 mg / mL, 50 mg / mL, 60 mg / mL, 80 mg / mL, or any range between two of the above values. Within this mass concentration range, it is more advantageous for the dispersion of the N-type inorganic nanoparticles and their spin-coating into the electronic functional layer 40. It should be noted that the mass concentration can also be appropriately adjusted outside the above range, so that the N-type inorganic nanoparticles and the crosslinking agent can be deposited to form the electronic functional layer 40.
[0083] In some embodiments, the mass ratio of the N-type inorganic nanoparticles to the crosslinking agent in the first mixture is (90~99):(1~10), for example, it can be 90:10, 92:8, 95:5, 98:2, 99:1, or any range between two of the above ratios. Within the range of the mass ratio, the crosslinking agent can effectively promote the crosslinking of the N-type inorganic nanoparticles, improve the stability of the electronic functional layer 40, and prevent it from being eroded and dissolved by the solvent during the subsequent spin-coating preparation of the interface layer 50.
[0084] In some embodiments, after depositing the first mixture, the process further includes performing a first annealing treatment. The temperature of the first annealing is 60°C to 160°C, for example, it can be 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, or any range between two of the above values; the time of the first annealing is 1 min to 60 min, for example, it can be 1 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, or any range between two of the above values.
[0085] Thus, under the aforementioned first annealing conditions, it is beneficial to remove the first solvent in the first mixture, promote the crosslinking agent to crosslink and connect the N-type inorganic nanoparticles, and obtain an electronic functional layer 40 with better film quality and higher stability.
[0086] In some embodiments, the method of forming an interface layer 50 on the electronic functional layer 40 and / or forming an interface layer 50 on the cathode 60 includes: vapor deposition or vapor deposition.
[0087] Furthermore, the target material for vapor deposition includes the first metal salt and the second metal salt; the vapor deposition temperature is 130℃~140℃, for example, it can be 130℃, 132℃, 135℃, 138℃, 140℃ or any range between two of the above values; the vapor deposition rate is 0.1nm / s~1nm / s, for example, it can be 130℃, 132℃, 135℃, 138℃, 140℃ or any range between two of the above values. Thus, under the aforementioned vapor deposition conditions, an interface layer 50 with high film quality can be prepared.
[0088] In other embodiments, the method of forming the interface layer 50 on the electronic functional layer 40 includes: A second mixture is provided, the second mixture comprising the first metal salt, the second metal salt, and the second solvent; The second mixture is deposited to obtain the interface layer 50.
[0089] Furthermore, in some embodiments, the second solvent comprises a polar solvent. Further, the polar solvent is selected from C1-C2. 10 Alcohol solvents. Furthermore, the C1-C... 10 The alcohol solvent is selected from one or more of methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, trimethoxybutanol, triethylene glycol monobutyl ether, and diethylene glycol dimethyl ether.
[0090] In some embodiments, the mass concentration of the first metal salt in the second mixture is 5 mg / mL to 50 mg / mL, for example, it can be 5 mg / mL, 10 mg / mL, 20 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL, or any range between two of the above values. Within the aforementioned mass concentration range, it is more advantageous for the first metal salt to be dispersed and spin-coated into the interface layer 50. It should be noted that the concentration can also be appropriately adjusted outside the aforementioned range, as long as the first and second metal salts are deposited to form the interface layer 50.
[0091] In some embodiments, the mass ratio of the first metal salt to the second metal salt in the second mixture is (1~4):(1~4), for example, it can be 1:4, 2:3, 1:1, 3:2, 4:1, or any range between two of the above ratios. Within the range of the mass ratio, the first metal salt and the second metal salt work together to effectively reduce the turn-on voltage of the optoelectronic device 100, improve the luminous efficiency of the optoelectronic device 100, and extend the service life of the optoelectronic device 100.
[0092] In some embodiments, after depositing the second mixture, the process further includes performing a second annealing treatment. Further, the temperature of the second annealing is 60°C to 160°C, for example, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, or any range between two of the above values; the time of the second annealing is 1 min to 30 min, for example, 1 min, 5 min, 10 min, 20 min, 30 min, or any range between two of the above values.
[0093] Thus, under the aforementioned second annealing conditions, it is beneficial to remove the second solvent from the second mixture, promoting the formation of a high-quality electronic functional layer 40 from the first metal salt and the second metal salt.
[0094] In some embodiments, after forming the interface layer 50, the method further includes placing the interface layer 50 in an aqueous environment.
[0095] Furthermore, the relative humidity of the aqueous environment is 40%~60%RH, for example, it can be 40%RH%, 45%RH%, 50%RH%, 55%RH%, 60%RH, or any range between two of the above values. The time for placing the interface layer 50 in the aqueous environment is 1min~180min, for example, it can be 1min, 5min, 10min, 30min, 60min, 100min, 120min, 150min, 180min, or any range between two of the above values. Thus, under the above conditions, it is beneficial for the first metal salt to absorb water molecules from the aqueous environment. Water molecules may promote the reaction between the first metal salt in the interface layer 50 and the first metal electrode of the cathode 60 to generate compounds with lower electron injection rates, or water molecules may promote the reaction between the N-type inorganic nanoparticles in the electronic functional layer 40 and the first metal electrode of the cathode 60 to reduce electron injection, thereby significantly improving the lifetime of the optoelectronic device 100.
[0096] It should be noted that, since the N-type inorganic nanoparticles in the electronic functional layer 40 are cross-linked by a cross-linking agent, they are not easily dissolved or eroded by the second solvent, thus ensuring the stability of the electronic functional layer 40.
[0097] In some embodiments, after forming the cathode 60 on the interface layer 50, and / or after sequentially forming the electronic functional layer 40, the light-emitting layer 30, and the anode 10 on the interface layer 50, the process further includes performing a heat treatment. The heat treatment refers to heat treatment of the entire fabricated prefabricated device.
[0098] Furthermore, the temperature of the heat treatment is 100℃~150℃, for example, it can be 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, or any range between two of the above values; the time of the heat treatment is 10min~60min, for example, it can be 10min, 20min, 30min, 40min, 50min, 60min, or any range between two of the above values. Thus, under the conditions of the heat treatment, it is beneficial for the release of water from the interface layer 50, and the water can act as an intermediate reaction medium to promote the reaction between the N-type inorganic nanoparticles and the first metal electrode. The water can be introduced by the material of the interface layer 50 through water absorption.
[0099] This application embodiment also provides a display device, which includes the above-described optoelectronic device 100.
[0100] The display device can be any electronic product with display function, including but not limited to smartphones, tablets, laptops, digital cameras, digital camcorders, smart wearable devices, smart weighing scales, in-vehicle displays, televisions, or e-book readers. Among them, smart wearable devices can be, for example, smart bracelets, smartwatches, virtual reality (VR) headsets, etc.
[0101] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.
[0102] Example 1 This embodiment provides an optoelectronic device, and the fabrication method of the optoelectronic device includes the following steps: Step S31: Clean the ITO conductive glass with a cleaning agent to initially remove the stains on the surface. Then, ultrasonically clean it for 20 minutes in deionized water, acetone, anhydrous ethanol, and deionized water respectively to remove the impurities on the surface. Finally, dry it with high-purity nitrogen to form an ITO anode with an average thickness of 30nm. Step S32: Spin-coat an aqueous solution of PEDOT:PSS (PEDOT to PSS molar ratio of 1:1) onto the ITO anode at a spin speed of 4000 rpm for 30 s, and then anneal at 150 °C for 30 min to form a hole injection layer with an average thickness of 20 nm. Step S33: Spin-coat an 8 mg / mL TFB chlorobenzene dispersion onto the hole injection layer at a spin speed of 3000 rpm for 30 s, and then anneal at 100 °C for 30 min to form a hole transport layer with an average thickness of 20 nm. Step S34: Spin-coat a 30 mg / mL quantum dot CdSe (PL=470 nm) n-octane dispersion onto the hole transport layer at a spin speed of 1500 rpm for 30 s, and then anneal at 80 °C for 10 min to form a light-emitting layer with an average thickness of 30 nm. Step S35: Dissolve 20 mg / mL ZnO in ethanol solvent, spin coat it onto the light-emitting layer at a speed of 3000 rpm for 30 s, and then anneal at 80 °C for 10 min to form an electron transport layer with an average thickness of 30 nm. Step S36: Deposit zinc acetate and magnesium acetate (mass ratio 1:1) onto the electron transport layer at a deposition pressure of 10. - 4 Pa, the evaporation temperature is 135℃, the evaporation rate is 0.5nm / s, the evaporation time is 4s, and an interface layer with an average thickness of 2nm is formed to obtain the prefabricated device. The prefabricated device is placed in an environment with a temperature of 25℃ and a relative humidity of 55RH% to absorb water for 10min. Step S37: After the prefabricated device in step S36 has absorbed water, it is placed in a vacuum coating machine. Ag target material is vapor-deposited on the electron transport layer to form a cathode with an average thickness of 35 nm. N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB) is vapor-deposited on the cathode to form a light extraction layer with an average thickness of 60 nm. Step S38: Perform tetrafluoroethylene encapsulation in an environment where both oxygen and water content are below 0.1 ppm, and heat treatment at 120°C for 30 min to obtain the optoelectronic device.
[0103] Example 2 This embodiment is basically the same as Embodiment 1, except that in step S35 of this embodiment, ZnO is replaced with magnesium-doped zinc oxide, and the molar fraction of magnesium doping is 5%.
[0104] Example 3 This embodiment is basically the same as Embodiment 1, except that in step S35 of this embodiment, ZnO is replaced with aluminum-doped zinc oxide, and the molar fraction of aluminum doping is 5%.
[0105] Example 4 This embodiment is basically the same as Embodiment 1, except that in step S35 of this embodiment, ZnO is replaced with SnO2.
[0106] Example 5 This embodiment is basically the same as Embodiment 1, except that in step S35 of this embodiment, ZnO is replaced with TiO2.
[0107] Example 6 This embodiment is basically the same as Embodiment 1, except that in step S37 of this embodiment, the cathode material is Ag and Mg (mass ratio of 1:1).
[0108] Example 7 This embodiment is basically the same as embodiment 1, except that in step S37 of this embodiment, the cathode material is Ag and Al (mass ratio of 1:1).
[0109] Example 8 This embodiment is basically the same as Embodiment 1, except that in step S36 of this embodiment, the mass ratio of zinc acetate to magnesium acetate is 4:1.
[0110] Example 9 This embodiment is basically the same as Embodiment 1, except that in step S36 of this embodiment, the mass ratio of zinc acetate to magnesium acetate is 1:4.
[0111] Example 10 This embodiment is basically the same as Embodiment 1, except that step S35 is replaced by step S35A and step S36 is replaced by step S36A. Step S35A: Dissolve 20 mg / mL ZnO in ethanol solvent and add pentaerythritol tetrakis(3-mercaptopropionic acid) ester, wherein the mass ratio of ZnO to pentaerythritol tetrakis(3-mercaptopropionic acid) ester is 100:5. Spin-coat the solution onto the light-emitting layer at a speed of 3000 rpm for 30 s. Then anneal at 100 °C for 20 min to form an electron transport layer with an average thickness of 30 nm. Step S36A: Dissolve zinc acetate and magnesium acetate (mass ratio 1:1) in ethanol solvent. The mass concentration of zinc acetate is 20 mg / mL. Spin coat the solution onto the electron transport layer at a speed of 3000 rpm for 30 s. Then anneal at 80°C for 5 min to form an interface layer with an average thickness of 2 nm.
[0112] Example 11 This embodiment is basically the same as that of Embodiment 10, except that in step S35A of this embodiment, pentaerythritol tetrakis(3-mercaptopropionic acid) is replaced with trimethylolpropane tris(3-mercaptopropionic acid).
[0113] Example 12 This embodiment is basically the same as that of Embodiment 10, except that in step S35A of this embodiment, the mass ratio of ZnO to pentaerythritol tetrakis(3-mercaptopropionic acid) ester is 100:1.
[0114] Example 13 This embodiment is basically the same as that of Embodiment 10, except that in step S35A of this embodiment, the mass ratio of ZnO and pentaerythritol tetrakis(3-mercaptopropionic acid) ester is 100:10.
[0115] Comparative Example 1 This comparative example is basically the same as Example 1, except that step S36 is not performed in this comparative example and the optoelectronic device does not contain an interface layer.
[0116] Comparative Example 2 This comparative example is basically the same as Example 1, except that in step S36 of this comparative example, only zinc acetate is vapor-deposited into the interface layer, and magnesium acetate is not vapor-deposited.
[0117] Comparative Example 3 This comparative example is basically the same as Example 1, except that in step S36 of this comparative example, only magnesium acetate is vapor-deposited into the interface layer, and zinc acetate is not vapor-deposited.
[0118] Comparative Example 4 This comparative example is basically the same as Example 10, except that step S35A is replaced with step S35 in Example 1, and in step S36, magnesium acetate is not added, and the material of the interface layer is zinc acetate.
[0119] The turn-on voltage, current efficiency CE, and lifespan T95 of the optoelectronic devices of Examples 1-13 and Comparative Examples 1-4 were tested. The test results are shown in Table 1.
[0120] The test method for the start-up voltage is as follows: the voltage value when the brightness reaches 1 nit is obtained using an efficiency test system built with Keithley 6485, which is the start-up voltage.
[0121] The current efficiency was calculated using a Keithley 2400 high-precision digital source meter, an Ocean Optic USB2000+ spectrometer, and an LS-160 luminance meter.
[0122] The test method for lifespan T95 is as follows: the time required for the brightness of the device to decrease to a certain percentage of the maximum brightness under a constant current of 2mA. The time for the brightness to decrease to 95% of the maximum brightness is defined as T95, and this lifespan is the measured lifespan.
[0123] Table 1
[0124] From Table 1, we can obtain: As can be seen from Examples 1-9 and Comparative Examples 1-4, an interface layer containing a first metal salt and a second metal salt is introduced between the electron transport layer and the cathode. The second metal salt effectively reduces the turn-on voltage of the optoelectronic device and improves its stability. Meanwhile, the first metal salt interacts with the cathode metal, and during energized operation, the metal salt or metal oxide generated by the reaction reduces the electron injection capability, effectively mitigating the effect of energizing on the electron transport layer material to improve electron transport rate, promoting dynamic charge balance, and effectively extending the service life of the optoelectronic device. As can be seen from Examples 10-13 and Comparative Examples 1-4, when preparing the interface layer by spin coating, in order to avoid the solvent of the interface layer from eroding the material of the electron transport layer, a crosslinking agent is introduced during spin coating of the electron transport layer. The crosslinking agent improves the density and stability of the electron transport layer, avoids the electron transport layer from being washed away by the solvent of the interface layer, and ensures that both the electron transport layer and the interface layer can be effectively prepared and function. Under the action of the interface layer, the optoelectronic devices of Examples 10-13 have a lower turn-on voltage, higher luminous efficiency, and longer service life.
[0125] The technical solutions provided by the embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. An optoelectronic device, characterized in that, It includes an anode, a light-emitting layer, an electronic functional layer, an interface layer, and a cathode arranged sequentially; The material of the electronic functional layer includes N-type inorganic nanoparticles; The material of the interface layer includes a first metal salt and a second metal salt. The metal ions in the first metal salt include fourth-period metal ions, and the metal ions in the second metal salt include one or more of alkali metal ions and alkaline earth metal ions. The cathode includes a first metal electrode.
2. The optoelectronic device as described in claim 1, characterized in that, The fourth-period metal ions include one or more of zinc ions, chromium ions, and manganese ions; The alkali metal ions include one or more of lithium ions, sodium ions, and potassium ions; The alkaline earth metal ions include one or more of magnesium ions and calcium ions. The anions in the first metal salt and the second metal salt each independently include one or more of the following: acetate ion, formate ion, propionate ion, oxalate ion, malonate ion, halide ion, nitrate ion, and sulfate ion. In the interface layer, the mass ratio of the first metal salt to the second metal salt is (1~4):(1~4).
3. The optoelectronic device as described in claim 1, characterized in that, The material of the first metal electrode includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, Mg, and Pt; The average particle size of the N-type inorganic nanoparticles is 3 nm to 15 nm. The N-type inorganic nanoparticles include one or more of the following: first doped metal oxide particles, first undoped metal oxide particles, non-metal nitrides, IIB-VIA group semiconductor materials, IIIA-VA group semiconductor materials, and IB-IIIA-VIA group semiconductor materials. The first undoped metal oxide particles are made of one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and HfO2. The metal oxides in the first doped metal oxide particles are made of one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, HfO2, and Al2O3. The doping elements in the doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, Cd, and Cs. The molar fraction of the doping elements in the first doped metal oxide particles is 1% to 20%. The non-metallic nitride includes Si3N4. The IIB-VIA group semiconductor material includes one or more of ZnS, ZnSe, and CdS. The IIIA-VA group semiconductor material includes one or more of InP and GaP. The IB-IIIA-VIA group semiconductor material includes one or more of CuInS and CuGaS.
4. The optoelectronic device as described in claim 1, characterized in that, The materials in the optoelectronic device further include a third metal salt and a first metal, wherein the third metal salt and the first metal are obtained by reacting the first metal salt with the first metal electrode, the third metal salt is located in the cathode, and the first metal is located in the interface layer; optionally, the third metal salt includes one or more of aluminum salt, silver salt, copper salt, molybdenum salt, gold salt, barium salt, calcium salt, ytterbium salt, magnesium salt, and platinum salt, and the first metal includes one or more of zinc, chromium, and manganese; The materials in the optoelectronic device further include a metal oxide and a second metal, which are obtained by reacting the N-type inorganic nanoparticles with the first metal electrode. The metal oxide is located between the interface layer and the cathode, and the second metal is located in the electronic functional layer. Optionally, the metal oxide includes one or more of aluminum oxide, silver oxide, copper oxide, molybdenum oxide, gold oxide, barium oxide, calcium oxide, ytterbium oxide, magnesium oxide, and platinum oxide, and the second metal includes one or more of zinc, titanium, tin, zirconium, tantalum, and hafnium.
5. The optoelectronic device as described in claim 1, characterized in that, The material of the electronic functional layer further includes a crosslinking agent; optionally, the crosslinking agent includes a multi-thiol crosslinking agent; the multi-thiol crosslinking agent includes one or more of pentaerythritol tetrakis(3-mercaptopropionic acid), tris[2-(3-mercaptopropoxy)ethyl isocyanurate], trimethylolpropane tris(3-mercaptopropionate), and dipentaerythritol hexa(3-mercaptopropionic acid); In the electronic functional layer, the mass ratio of the N-type inorganic nanoparticles to the crosslinking agent is (90~99):(1~10).
6. The optoelectronic device as described in claim 1, characterized in that, The average thickness of the electronic functional layer is 10 nm to 100 nm. The average thickness of the interface layer is 0.5 nm to 10 nm; The average thickness of the cathode is 20 nm to 200 nm. The anode comprises one or more of a second metal electrode, a carbon material electrode, a metal oxide electrode, and a composite electrode. The material of the second metal electrode comprises one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, and Mg. The material of the carbon material electrode comprises one or more of graphite, carbon nanotubes, graphene, and carbon fibers. The material of the metal oxide electrode comprises one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3, and AMO. The composite electrode is a composite electrode in which a metal layer is sandwiched between layers of doped or undoped transparent metal oxide particles. The composite electrode comprises AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2. The material of the light-emitting layer includes organic light-emitting materials or quantum dots; the organic light-emitting material is selected from 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridinium(III)], 4,4',4''-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridinium], diaromatic anthracene derivatives, stilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescence materials, TTA materials, and TADF. The material comprises one or more of the following: a polymer containing BN covalent bonds, an HLCT material, and an Exciplex luminescent material; the quantum dot is selected from one or more of the following: a single-structure quantum dot, a core-shell quantum dot, and a perovskite quantum dot; the material of the single-structure quantum dot, the core material of the core-shell quantum dot, and the shell material of the core-shell quantum dot are respectively selected from one or more of the following: group II-VI compounds, group IV-VI compounds, group III-V compounds, and group I-III-VI compounds; the shell of the core-shell quantum dot comprises one or more layers; the... Group II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, H gSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, Cd ZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe; wherein the IV-VI compound is selected from one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe;The III-V compounds are selected from one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. Multiple types; the I-III-VI group compounds are selected from one or more of CuInS2, CuInSe2, and AgInS2; the core-shell structured quantum dots are selected from one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS, and InP / ZnSe / ZnS; the perovskite quantum dots are made of doped or undoped inorganic perovskite semiconductors or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has the general structural formula AMX3, where A is Cs; + Ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ Cu 2+ Ni 2+ Cd 2+ Cr 2+ Mn 2+ Co 2+ Fe 2+ 、Ge 2+ Yb 2+ Eu 2+ One or more of the following, where X is a halide anion selected from Cl... - ,Br - I - One or more of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, where B is an organic amine cation selected from CH3(CH2). n-2 NH3 + Or [NH3(CH2)] n NH3] 2+ Where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ Cu 2+ Ni 2+ Cd 2+ Cr 2+ Mn 2+ Co 2+ Fe 2+ 、Ge 2+ Yb 2 + Eu 2+ One or more of the following, where X is a halide anion selected from Cl... - ,Br - I - One or more of the following; The optoelectronic device further includes a hole functional layer located between the anode and the light-emitting layer; the hole functional layer includes one or more of a hole injection layer and a hole transport layer, the hole injection layer being located between the anode and the hole transport layer; the material of the hole injection layer is selected from one or more of high-conductivity organic molecular materials, transition metal oxides, and transition metal sulfide compounds; the high-conductivity organic molecular material is selected from poly(3,4-ethylenedioxythiophene), poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,1 2-Hexaazabenzanphenanthrene, polyester copper carbonate, free phthalocyanine, copper phthalocyanine, platinum phthalocyanine, titanium phthalocyanine, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazabenzanphenanthrene, 7,7,8,8-tetracyano-p-benzoquinone dimethyl ether, N,N'-bis[4-(diphenylamino)phenyl]-N,N'-di-1-naphthyl-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-di(4'-(N,N-di(1-naphthyl)-amino)-4-biphenyl)-biphenylamine, N,N′-di(phenyl)-N,N′-di(4′-(N,N-di(phenylamino)-4-biphenyl)-biphenylamine, N,N'-diphenyl-N,N'-di-[4-(N,N- [di-p-tolylamino]phenyl]benzidine, N4,N4,N4',N4'-tetra(4-methoxyphenyl)-[1,1'-biphenyl]-4,4'-diamine, 4,4',4''-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, 4,4'4"-tris(N,N-diphenylamino)triphenylamine, N2,N2'-(9,9-dimethyl-9H-fluorene-2,7-diyl)bis(9,9-dimethyl-N2,N7,N7-triphenyl-9H-fluorene-2,7-diamine), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone; the transition metal oxide is selected from NiO, MoO3, WO3, CuO, Cu2O. One or more of the following; the transition metal chalcogenide compound is selected from one or more of MoS2, MoSe2, WS3, WSe3, and CuS; the material of the hole transport layer includes one or more of organic hole transport materials and inorganic hole transport materials, wherein the organic hole transport material includes poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), poly(9-vinylcarbazole), 9,9'-(1,3-phenyl)bis-9H-carbazole, 4,4',4''-tris(carbazole-9-yl)triphenylamine, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, N,N'-Di(naphthyl-2-yl)-N,N'-Di(phenyl)biphenyl-4,4'-diamine, N2,N7-Di-1-naphthyl-N2,N7-diphenyl-9,9'-spirodi[9H-fluorene]-2,7-diamine, N2,N7-DI-1-naphthyl-N2,N7,9,9-tetraphenyl-9H-fluorene-2,7-diamine, 9,9-di(2-ethylhexyl)-N,N'-di-1-naphthyl-N,N'-diphenyl-9H-fluorene-2,7-diamine, N4,N4'-di(4-vinylphenyl)-N4,N4'-di-1-naphthylbiphenyl-4,4'-diamine, 3,6-bis(9-phenyl-9H- Carbazole-3-yl)-9-phenyl-9H-carbazole, 9,1-dihydro-9,9-dimethyl-1-(9-phenyl-9H-carbazole-3-yl)-idine, N-biphenyl-4-yl-9,9-dimethyl-N-[4-(9-phenyl-9H-carbazole-3-yl)phenyl]-9H-fluorene-2-amine, 9,9-dimethyl-N,N'-bis(3-methylphenyl)-N,N'-diphenyl-9H-fluorene-2,7-diamine, N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-diphenyl-9,9-spirodi Fluorene-2,7-diamine, N,N,N',N'-tetra(2-naphthyl)-1,1'-biphenyl-4,4'-diamine, 2,2',7,7'-tetra(diphenylamino)-9,9'-spirobisfluorene, N,N'-bis(9,9-dimethyl-9H-fluorene-2-yl)-N,N'-diphenylbenzidine, N,N,N',N'-tetraphenylbenzidine, 4,4'-(diphenylmethylene)bis(N,N-diphenylaniline), 9,9-bis[4-[bis(bisphenyl-4-yl)amino]phenyl]fluorene, tris(4-biphenyl)amine, 4,4'-(diphenylsilanediyl)bis(N,N-diphenylaniline), 4,4' -(9H-fluorene-9-alkylene)bis[N,N-bis(4-methylphenyl)-benzylamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine, poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4'-bis(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, wherein the inorganic hole transport material includes doped graphene, undoped graphene, C, 60 The metal oxide particles are selected from one or more of the following: a second doped metal oxide particle, a second undoped metal oxide particle, a metal sulfide, a metal selenide, and a metal nitride. The metal oxides in the second doped metal oxide particle and the second undoped metal oxide particle each independently include one or more of MoO3, WO3, NiO, CrO3, CuO, Cu2O, and V2O5. The doping element in the second doped metal oxide particle includes one or more of Mo, W, Ni, Cr, Cu, and V. The metal sulfide includes one or more of CuS, MoS3, and WS3. The metal selenide includes one or more of MoSe3 and WSe3. The metal nitride includes p-type gallium nitride.
7. A method for fabricating an optoelectronic device, characterized in that, Includes the following steps: It provides an anode, a light-emitting layer, and an electronic functional layer arranged sequentially; An interface layer is formed on the electronic functional layer; A cathode is formed on the interface layer to obtain a photoelectric device; or, Provide cathode; An interface layer is formed on the cathode; An electronic functional layer, a light-emitting layer, and an anode are sequentially formed on the interface layer to obtain an optoelectronic device. The electronic functional layer is made of N-type inorganic nanoparticles; the interface layer is made of a first metal salt and a second metal salt, wherein the metal ions in the first metal salt include fourth-period metal ions, and the metal ions in the second metal salt include one or more of alkali metal ions and alkaline earth metal ions; and the cathode includes a first metal electrode.
8. The preparation method according to claim 7, characterized in that, The method for preparing the electronic functional layer in the sequentially arranged anode, light-emitting layer, and electronic functional layer includes: providing a first mixture comprising the N-type inorganic nanoparticles, a crosslinking agent, and a first solvent; depositing the first mixture to obtain the electronic functional layer; wherein... The crosslinking agent includes a multi-thiol crosslinking agent; the multi-thiol crosslinking agent includes one or more of pentaerythritol tetrakis(3-mercaptopropionic acid), tris[2-(3-mercaptopropionyloxy)ethyl isocyanurate], trimethylolpropane tris(3-mercaptopropionate), and dipentaerythritol hexa(3-mercaptopropionic acid); The first solvent includes a polar solvent, which is selected from C1-C2. 10 Alcohol solvents; the C1-C 10 The alcohol solvent is selected from one or more of methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, trimethoxybutanol, triethylene glycol monobutyl ether, and diethylene glycol dimethyl ether; In the first mixture, the mass concentration of the N-type inorganic nanoparticles is 10 mg / mL to 80 mg / mL; In the first mixture, the mass ratio of the N-type inorganic nanoparticles to the crosslinking agent is (90~99):(1~10). After depositing the first mixture, the process further includes: performing a first annealing treatment; optionally, the temperature of the first annealing is 60℃~160℃, and the time of the first annealing is 1min~60min.
9. The preparation method according to claim 7 or 8, characterized in that, The method for forming an interface layer on the electronic functional layer includes: providing a second mixture comprising a first metal salt, a second metal salt, and a second solvent; depositing the second mixture to obtain the interface layer; wherein... The first metal salt includes one or more of a first organic acid salt and a first inorganic acid salt; optionally, the organic acid salt includes one or more of zinc acetate, zinc formate, zinc propionate, chromium acetate, chromium formate, chromium propionate, manganese acetate, manganese formate, and manganese propionate, and the inorganic acid salt includes one or more of zinc chloride, zinc nitrate, zinc sulfate, chromium chloride, chromium nitrate, chromium sulfate, manganese chloride, manganese nitrate, and manganese sulfate. The second metal salt includes one or more of a second organic acid salt and a second inorganic acid salt; optionally, the organic acid salt includes one or more of lithium acetate, lithium formate, lithium propionate, lithium oxalate, lithium malonate, sodium acetate, sodium formate, sodium propionate, sodium oxalate, sodium malonate, potassium acetate, potassium formate, potassium propionate, potassium oxalate, potassium malonate, magnesium acetate, magnesium formate, magnesium propionate, magnesium oxalate, magnesium malonate, calcium acetate, calcium formate, calcium propionate, calcium oxalate, calcium malonate; and the inorganic acid salt includes one or more of lithium chloride, lithium bromide, lithium fluoride, lithium nitrate, lithium sulfate, sodium chloride, sodium bromide, sodium sulfate, sodium nitrate, potassium chloride, potassium bromide, potassium sulfate, potassium nitrate, magnesium chloride, magnesium nitrate, magnesium sulfate, calcium chloride, calcium nitrate, and calcium sulfate. The second solvent includes a polar solvent selected from C1-C2. 10 Alcohol solvents; the C1-C 10 The alcohol solvent is selected from one or more of methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, trimethoxybutanol, triethylene glycol monobutyl ether, and diethylene glycol dimethyl ether; In the second mixture, the mass concentration of the first metal salt is 5 mg / mL to 50 mg / mL; In the second mixture, the mass ratio of the first metal salt to the second metal salt is (1~4):(1~4). After depositing the second mixture, the process further includes: performing a second annealing treatment; the temperature of the second annealing is 60℃~160℃, and the time of the second annealing is 1min~30min.
10. The preparation method according to claim 7, characterized in that, The method of forming an interface layer on the electronic functional layer and / or forming an interface layer on the cathode includes: vapor deposition; optionally, the target material for vapor deposition includes the first metal salt and the second metal salt; the vapor deposition temperature is 130℃~140℃, and the vapor deposition rate is 0.1nm / s~1nm / s; After forming the interface layer, the method further includes: placing the interface layer in a water-containing environment; optionally, the relative humidity of the water-containing environment is 40RH%~60RH%, and the time for placing the interface layer in the water-containing environment is 1min~180min. After forming a cathode on the interface layer, and / or after sequentially forming an electronic functional layer, a light-emitting layer, and an anode on the interface layer, the method further includes: performing a heat treatment; optionally, the temperature of the heat treatment is 100℃~150℃, and the time of the heat treatment is 10min~60min.